Transformative pedagogies for teacher education : critical action, agency and dialogue in teaching and learning contexts - Lopez, Ann E.; Olan, Elsie Lindy (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"This is the second book in the series Transformative Pedagogies for Teacher Education. Like the first book in the series it is geared towards practitioners in the field of teacher education. This second book focuses on action, agency and dialogue. It features chapters by a collection of teacher educators, researchers, teacher advocates and practitioners drawing on their research and experiences with teacher candidates to explore critical issues in teacher education. The book will be useful to teacher educators working with teacher candidates in different contexts, particularly diverse contexts. Given demographic shifts and the need for educators to respond to growing diversity in schools, educators will find valuable strategies in this book they can implement in their own practice. In addition to valuable strategies, authors explore different approaches and perspectives in teacher education in the preparation of teacher candidates for a changing world. Critical notions of education are posited from different perspectives and locations. This book will be useful for schools, school boards and districts engaging in ongoing professional development of teachers. It will also be of value to school leaders and aspiring leaders in principal preparation programs as working with new teachers and teacher educators is an integral part of their role"-- Provided by publisher.
Keywords: Teachers -- Training of.; Teaching -- Social aspects.; Education and globalization.; Multicultural education.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books